A influência das redes sociais na obtenção de votos: eleições para governadores de 2018 - Souza, Paulo Henrique Rocha de (2019)
This research aims to investigate the influence of political, personal, and activity on the Facebook social network in obtaining votes by candidates for the position of State Governor for the first round of the 2018 election. To this, an empirical study is conducted in which the obtained data are estimated by the Quantile Regression method, which allows to analyze the impacts of the explanatory variables on the dependent variable through appropriate estimates, being adequate for the characteristic of the majority election system in which the first round result can be be obtained in different parts of the distribution of votes. From the analysis performed it is possible to verify the influence of the various variables used, whether they are personal characteristics, electoral / party characteristics, and the use of social network, the amount of votes received by candidates in the electoral dispute in question. Among the results found is the positive influence of the number of Facebook followers of candidates on the amount of votes obtained, which demonstrates the importance of digital influence on election results and the democratic process.